Effects of Kefir on the Cardiac Autonomic Tones and Baroreflex Sensitivity in Spontaneously Hypertensive Rats - Klippel, Brunella F.; Duemke, Licia B.; Leal, Marcos A.; Friques, Andreia G. F.; Dantas, Eduardo M.; Dalvi, Rodolfo F.; Gava, Agata L.; Pereira, Thiago M. C.; Andrade, Tadeu U.; Meyrelles, Silvana S.; Campagnaro, Bianca P.; Vasquez, Elisardo C. (Frontiers in Physiology, 2016)
It has been previously shown that the probiotic kefir (a symbiotic matrix containing acid bacteria and yeasts) attenuated the hypertension and the endothelial dysfunction in spontaneously hypertensive rats (SHR). In the present study, the effect of chronic administration of kefir on the cardiac autonomic control of heart rate (HR) and baroreflex sensitivity (BRS) in SHR was evaluated. Methods: SHR were treated with kefir (0.3 mL/100 g BW) for 60 days and compared with non-treated SHR and with normotensive Wistar-Kyoto rats. Cardiac autonomic vagal (VT) and sympathetic (ST) tones were estimated through the blockade of the cardiac muscarinic receptors (methylatropine) and the blockade of β1-adrenoceptor (atenolol). The BRS was evaluated by the tachycardia and bradycardia responses to vasoactive drug-induced decreases and increases in arterial blood pressure (BP), respectively. Additionally, spontaneous BRS was estimated by autoregressive spectral analysis. Results: Kefir-treated SHR exhibited significant attenuation of basal BP, HR and cardiac hypertrophy compared to non-treated SHR (12, 13 and 21%, respectively). Cardiac VT and ST were significantly altered in the SHR ( 40 and 90 bpm) compared with Wistar rats ( 120 and 30 bpm) and were partially recovered in SHR-kefir ( 90 and 25 bpm). SHR exhibited an impaired bradycardic BRS ( 50%) compared with Wistar rats, which was reduced to 40% in the kefir-treated SHR and abolished by methylatropine in all groups. SHR also exhibited a significant impairment of the tachycardic BRS ( 23%) compared with Wistar rats and this difference was reduced to 8% in the SHR-kefir. Under the action of atenolol the residual reflex tachycardia was smaller in SHR than in Wistar rats and kefir attenuated this abnormality. Spectral analysis revealed increased low frequency components of BP ( 3.5-fold) and pulse interval ( 2-fold) compared with Wistar rats and these differences were reduced by kefir-treatment to 1.6- and 1.5-fold, respectively. Spectral analysis also showed an impairment of spontaneous BRS in SHR, but kefir-treatment caused only a tendency to reverse this result. Conclusions: The novelty of this study is that daily chronic consumption of a low dose of kefir reduced the impairment of the cardiac autonomic control of HR and of the impaired BRS in SHR